EFFICACY OF TOOTH BRUSHES OF DIFFERENT BRISTLES DESIGN IN PLAQUE REMOVAL - Muhammad Kashif; Alia Rani Sial; Urooj Mujahid et al. (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: To evaluate the efficacy of four different deigns of manual tooth brushes available in the market, with respect to plaque removal efficacy. MATERIALS AND METHODS: It was an interventional kind of study that was examiner blind. 30 volunteers from the same age group (19 to 25 years) participated. Four brushes were selected to be checked and compared for efficacy and were given codes that were revealed only at the end of the study. For the quantitative (Percentage reduction) assessment of plaque, Gilmore-Glickman Modification of Hein Plaque Index was chosen. RESULTS: Flat-bristle designed toothbrush showed a total reduction of 57%. For Concave-bristle designed toothbrush, the value changed from 112.67 to 47.63 with a reduction of 57.67%. Zigzag bristle designed toothbrush showed a Post-brushing mean plaque score of 54.07 compared to 117.57 (mean pre-brushing score) giving rise to a reduction of 54.01%. Whereas crisscross bristle designed tooth brush showed a post-brushing plaque score of 75.00, compared to 109.46 (prebrushing mean plaque score) with a total reduction of the value 31.48%. This suggests that all the four toothbrushes have shown plaque reduction, somehow to a greater or lesser extent. The reduction was also found to be statistically significant as the p-values were less than 0.05. CONCLUSION: Based on the results obtained from the study it comes forward that though newer and newer varieties of toothbrush bristle designs are coming in the market, no one is exceptional in efficacy for removing plaque.